Retinopathy in patients with falciform disease: a literature review (Research, Society and Development, 2020)
Objective: Describe the factors that trigger retinopathy in sickle cell disease. Method: an integrative bibliographic review with a qualitative approach was used, using the VHL, Scielo, PUBMED, and LILACS digital databases as a data source, respecting the time frame from 2005 to 2020, where 40 articles were found, which were read. titles and abstracts, and from that, 13 were used for the results, these, in turn, were organized into three categories and then analyzed and discussed. Results: After reading and analyzing the data, it was possible to verify that there is a marked incidence of sickle cell retinopathy, which affects between 10 and 20% of sickle cell patients in different age groups and all pathology subtypes, being more frequent in the SC group and soon after SS, respectively, linked to this, it was possible to verify that the main factor for the emergence of retinopathy in sickle cell disease is the occurrence of vaso-occlusive phenomena of macro and microcirculation, such phenomena end up compromising retinal oxygenation. Conclusion: It is noteworthy that the objective and problems that guided this study were addressed, however, it has gaps that can be answered and explored further from another point of view, but from it, there was a lack of studies current in Brazil that address sickle cell retinopathy.